Find, group, link: the promises of the RDA - Anglada, Lluís (Anuario ThinkEPI, 2016)
In 2016, the first Spanish libraries will begin using RDA cataloging rules (Resource Description and Access), replacing AACR2. This note article explains that RDA should be viewed as a confluence of three trends: savings, sharing, and developing technology. The objectives of the catalogs (to find a known work, to find works by the same author or subject, and to provide relationships between authors or entities) are explained. A brief historical review of AACR, MARC format, ISBD, FRBR, and Bibframe, is made, finally, to explain the RDA rules.